A placebo-controlled trial of acotiamide for meal-related symptoms of functional dyspepsia. Issue 6 (9th December 2011) - Matsueda, Kei; Hongo, Michio; Tack, Jan; Saito, Youichi; Kato, Hiroki
Abstract : Objective: To determine the efficacy of acotiamide, an acetylcholinesterase inhibitor, in patients with functional dyspepsia (FD) in a 4-week trial Methods: A multicentre, randomised, placebo-controlled, parallel-group, phase III trial was carried out, in which patients with FD received 100 mg of acotiamide or placebo three times a day for 4 weeks, with 4 weeks post-treatment follow-up. The primary efficacy end points were global assessment of overall treatment efficacy (OTE) and elimination rate of all three meal-related symptoms (postprandial fullness, upper abdominal bloating and early satiation), as derived from daily diaries. Secondary efficacy end points were individual symptom scores and quality of life. Adverse events were monitored. Results: 52.2% of those receiving acotiamide and 34.8% in the placebo group (p<0.001) were classified as responders according to a global assessment of OTE. Over 4 weeks, the elimination rate for all three meal-related symptoms was 15.3% among patients receiving acotiamide compared with 9.0% in the placebo group (p=0.004). The significant benefit of acotiamide over placebo in OTE and elimination rate was maintained during the 4 week post-treatment follow-up. All other secondary efficacy end points, including quality of life, were significantly improved with 100 mg of acotiamide as compared with placebo. The number needed to treat was 6 for OTE and 16 for symptom elimination rate. The incidence of adverse events was similar between the acotiamide group and placebo group and no significant cardiovascular effects due to treatment were seen. Conclusions: Over 4 weeks, acotiamide significantly improved symptom severity and eliminated meal-related symptoms in patients with FD. Trial registration number: http://ClinicalTrials.gov number, NCT00761358 .